2019
DOI: 10.17759/pse.2019240301
|View full text |Cite
|
Sign up to set email alerts
|

Life Models in Young People: Ideas of Future Family and Impacts of Parental Models

Abstract: The article substantiates the introduction of the “life model” construct as a fragment of life scenario in a specific area of human life and describes the development of tools for its study. The results of a study on life models of relationships in young people (on a sample of 100 students of St. Petersburg State University, the average age of 21 ± 1.1 years) are presented by the following parameters: the need for creating a family and maintaining close relationships; understanding the nature of relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In the boundary stages of the individual's existence (childhood and old age) the family is a support, a kind of psychological compensator of limited human possibilities. Moskvicheva, Rean, Kostromina, Grishina, and Zinovieva (2019) in the study of the life patterns of young people came to the following conclusion.…”
Section: Problem Statementmentioning
confidence: 93%
“…In the boundary stages of the individual's existence (childhood and old age) the family is a support, a kind of psychological compensator of limited human possibilities. Moskvicheva, Rean, Kostromina, Grishina, and Zinovieva (2019) in the study of the life patterns of young people came to the following conclusion.…”
Section: Problem Statementmentioning
confidence: 93%
“…A number of studies are aimed at studying the inner world of the family, the dynamics of its development (Hess & Handel, 2016;Widmer, 2016), the influence of the home environment (microclimate) on the attitude towards the family (Dobriakov et al, 2020;Nartova-Bochaver et al, 2018). Rean (2018), Kuperberg (2019), Cheung et al (2019), Moskvicheva et al (2019) and others raise issues related to the functioning of the family as a system, changing the place of the family in the hierarchy of values, and the attitude of young people to the family as a value. However, there are practically no works examining the influence of the family subculture on the vital activity and attitudes of all family members.…”
Section: Problem Statementmentioning
confidence: 99%
“…In society, more and more often there is an opinion that the family is being destroyed, traditional values (love, care, empathy, responsibility for children) are leaving it, the readiness of young people to have children is decreasing, intra-family relations are becoming more complicated (conflicts, misunderstanding, loneliness in the family), the number of illegitimate births is increasing and, as a consequence, the presence of incomplete families. At the same time, a number of studies present results that testify to the preservation of the influence of the family on the value attitudes of young people in the structure of their life values (Moskvicheva et al, 2019). The family remains for a person that "island" where he can receive help, support, protection, not to mention the child, for whom the family acts as an environment for primary socialization.…”
Section: Introductionmentioning
confidence: 99%
“…The research interest shown by the Russian authors in the problems of the paternal families can be observed in the analysis of the causes and typology of the male monoparenthood, characteristics of a social portrait of the single father with children, experienced difficulties, educational practices [4][5][6][7][8][9][10], contradictory generation of "caring" masculinity and involved fatherhood [11,12] as well as in the study of protection of rights, technologies, and measures enabling to support the single fathers as new clients of the social services [6,8,13]. Deficient researches and poor studies of the single fathers as a social group give rise to its polar assessments: from positive heroic images of forced single fatherhood due to severe illness, death, or deviance of the mother [14] to negative ones relating to the fathers estranged or underperforming their parental responsibilities [8,15].…”
Section: Introductionmentioning
confidence: 99%